2014
DOI: 10.1097/grf.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pessary Use and Preterm Birth

Abstract: Preterm birth remains a considerable public health concern and priority. Little headway has been made in the prevention of preterm birth despite considerable research in this area. New ideas and treatments are desperately needed. The pessary has emerged as a possible treatment for the prevention of preterm birth in both singleton and twin gestations. It appears to be low cost with minimal side effects. This review focuses on the available evidence for the use of cervical pessaries for the prevention of preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…This meta-analysis showed that cervical pessary had no significant adverse effects on respiratory distress syndrome, necrotising enterocolitis, intraventricular haemorrhage, neonatal sepsis, and perinatal death, among others. No serious side effects were reported in these trials 13 15 16 , which is consistent with all the published studies 21 . The most common side effects of cervical pessary placement are an increase in vaginal discharge and pain during the pessary insertion and removal 21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This meta-analysis showed that cervical pessary had no significant adverse effects on respiratory distress syndrome, necrotising enterocolitis, intraventricular haemorrhage, neonatal sepsis, and perinatal death, among others. No serious side effects were reported in these trials 13 15 16 , which is consistent with all the published studies 21 . The most common side effects of cervical pessary placement are an increase in vaginal discharge and pain during the pessary insertion and removal 21 .…”
Section: Discussionsupporting
confidence: 91%
“…No serious side effects were reported in these trials 13 15 16 , which is consistent with all the published studies 21 . The most common side effects of cervical pessary placement are an increase in vaginal discharge and pain during the pessary insertion and removal 21 . Moreover, in the trial by Goya et al .…”
Section: Discussionsupporting
confidence: 91%
“…fFN testing remains valid in the presence of a cerclage, although has a higher false‐positive rate than does testing without cerclage. Sonographic assessment of the cervix with a pessary in situ can be technically challenging, and may require placement of the probe in the center of the pessary to achieve adequate images. The role of sonographic CL surveillance following pessary placement has not been elucidated, nor has fFN assessment been validated in patients with a pessary in situ .…”
Section: Epidemiology and Definitionsmentioning
confidence: 99%
“…4,5 The low cost and relative ease of insertion and removal as well as avoidance of medication exposure or operative procedure have been factors driving further investigation of the effectiveness of the cervical pessary. 6,7 Because the Arabin pessary is constructed in such a way that the caudal portion of the device encircles the cervix, some have postulated that it may provide additional benefit by also preventing cervical dilation, deterioration of the mucous plug, and exposure of the membranes. 8 The Arabin pessary appears to be associated with low rates of major complications.…”
mentioning
confidence: 99%